Sound absorption properties of porous concrete layers for noise barrier - Galip, N S; Haron, Z; Mohamed, R N; Darus, N; Zamri, N F; Yahya, M N; Yahya, K; Din, N C; Kassim, A S F A; Redzuan, I H; Jahya, Z (2023)
The porous concrete layer is an open pore material placed on the noise incident face of a sound barrier structure on the road. Pore characteristics such as diameter, area and distribution are the main characteristics of porous concrete different from conventional concrete and play a dominant role in sound absorption properties. Factors affecting the pore structure of typical porous concrete have been discussed. The effects of macroscopic properties on sound absorption properties such as maximum sound absorption coefficient (SAC max), noise reduction and noise average were reviewed. The porous concrete containing other types of aggregate such as recycle, waste material, and lightweight in porous concrete innovation were discussed. Consequently, the effect of thickness, two layers and multiple layers of porous concrete to improve sound absorption at low frequencies. Finally, the guidances were proposed for the mixture composition for producing porous layer for good sound absorbing properties